9, 10-Bis((Z)-2-phenyl-2-(pyridin-2-yl)vinyl)anthracene: Aggregation-induced emission, mechanochromic luminescence, and reversible volatile acids-amines switching. (February 2018) - Sun, Qikun; Wang, Honghong; Xu, Xin; Lu, Yuansheng; Xue, Shanfeng; Zhang, Haichang; Yang, Wenjun
Abstract: Pyridine-containing luminophores have been attracting much attention due to pyridine functions in carrier transport and cation complexation. Here we prepared a butterfly-like molecule 9, 10-bis(2-phenyl-2-(pyridin-2-yl)vinyl)anthracene (PyVA ) for developing new multifunctional dyes. The multiple rotatable aryl groups enabledPyVA to exhibit a strong aggregation-induced emission effect, and the seriously twisted butterfly-like backbone rendered the solid weak intermolecular π-π interactions and mechanofluorochromism. Quantum chemical calculations indicated that protonation of the pyridyl units could narrow the band gap ofPyVA, and X-ray crystallography revealed thatPyVA molecules packed in a Z configuration in which the pyridyl units adopted a more twisted conformation with lone N -electron pairs stabilized by intra- and intermolecular CH···N and CH···π interactions. It was observed that both fluorescent crystalline and amorphousPyVA solids could sense volatile acids with a remarkably red-shifted emission, but the amorphous state was more sensitive. Moreover, the acidichromicPyVA solid could further sense volatile amines, and this alternative pH sensitive chromic process was reversible and applicable to fluorescence patterning. Graphical abstract: Highlights: Butterfly-like 9, 10-bis(2-phenyl-2-(pyridin-2-yl)vinyl)anthracene (PyVA) was designed and synthesized. PyVA exhibits aggregation-induced emission and mechanofluorochromism and reversible acidi- and alkali-chromic process. Compared with the crystalline state, the amorphous state was more sensitive for volatile acids.